2010
DOI: 10.1002/jso.21812
|View full text |Cite
|
Sign up to set email alerts
|

The CD40‐CD154 interaction would correlate with proliferation and immune escape in pancreatic ductal adenocarcinoma

Abstract: These results suggest that the CD40-CD154 interaction would correlate with cell proliferation and secretion of cytokines in PDAC cells, and CD154 overexpression could be a favorable prognostic factor in PDAC patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…The functional relevance of the CD40/CD40L interac tions in malignant tumors is variable and likely context dependent. It has been shown that CD40/CD40L interac tions or up-regulation of CD40 correlated with poor prognosis in pancreatic ductal carcinoma [14] and non-small lung cancer [15], whereas CD40 ligation exerts antiproliferative effects and apoptosis induction in malignant ovarian tumors [16] and melanoma cell lines [17]. Previous studies also showed that not only TNFα but also the CD40/CD40L interactions exert a direct cytotoxicity of HeLa CD40 cells in the presence of a protein inhibitor [9].…”
Section: Discussionmentioning
confidence: 99%
“…The functional relevance of the CD40/CD40L interac tions in malignant tumors is variable and likely context dependent. It has been shown that CD40/CD40L interac tions or up-regulation of CD40 correlated with poor prognosis in pancreatic ductal carcinoma [14] and non-small lung cancer [15], whereas CD40 ligation exerts antiproliferative effects and apoptosis induction in malignant ovarian tumors [16] and melanoma cell lines [17]. Previous studies also showed that not only TNFα but also the CD40/CD40L interactions exert a direct cytotoxicity of HeLa CD40 cells in the presence of a protein inhibitor [9].…”
Section: Discussionmentioning
confidence: 99%
“…235 The normal expression and interaction of CD40 and CD154 by immune cells result in the proliferation of the immune response with the potential to ultimately affect antitumor immunity. In a recent study by Shoji et al, 236 it was found that both CD40 and CD154 are expressed by PDAC cell lines and patient specimens, and although the study did not directly evaluate TILs, they found the frequency of CD154 expression on TILs to be low in their xenograft model. These findings suggest that PDAC cells can potentially use CD40 and CD154 expression as an autocrine mechanism to promote tumor cell proliferation as well as potentially alter CD154 expression on TILs.…”
Section: Immune Failure and Tumor Escape In Pdacmentioning
confidence: 97%
“…A good example of this was the finding that very high expression of CD154 in patient specimens correlated with a favorable prognosis. 236 On the one hand, PDAC cells promote their own growth with the expression of CD40-CD154 and immune cell suppression with secretion of IL-10. The ligation of CD40 on these tumor cells leads to the secretion of proinflammatory cytokines IL-6 and IL-12 that could ultimately result in an antitumor response.…”
Section: Immune Failure and Tumor Escape In Pdacmentioning
confidence: 99%
“…CD40 on the surface of APCs could bind with the CD40 ligand expressed on activated CD4+ T cells, thus forming a stimulatory loop. CD40 and its ligand (CD154) are both expressed in a subset of pancreatic patients, and the high expression of CD40 ligand is associated with significantly better prognosis than others [102]. The activation of CD40 with a CD40 agonist in combination with gemcitabine is indicated to promote accumulation of tumoricidal macrophages within the tumors in the KPC mouse model, which resulted in stromal collapse and tumor regression in the KPC mouse model and some advanced-stage pancreatic cancer patients [103,104].…”
Section: Immunotherapy and Other State-of-the-art Molecular Optionsmentioning
confidence: 99%